The Protective Effect of Mulberry Leaf Flavonoids on High-Carbohydrate-Induced Liver Oxidative Stress, Inflammatory Response and Intestinal Microbiota Disturbance in Monopterus albus - Yong Shi; Lei Zhong; Yuding Fan; Junzhi Zhang; Huan Zhong; Xiang Liu; Chuang Shao; Yi Hu (MDPI AG, 2022)
An 8-week feeding trial with high-carbohydrate- and 100, 200 and 300 mg/kg mulberry leaf flavonoids (MLF)-supplemented diets (HCF1, HCF2 and HCF3, respectively) was conducted to evaluate the protective effect of MLF on oxidized high-carbohydrate-induced glucose metabolism disorder, liver oxidative damage and intestinal microbiota disturbance in Monopterus albus. The results showed that HC diets had significant negative effects on growth, glucose metabolism, liver antioxidant and immunity, as well as intestinal microbiota, in comparison to CON diets. However, WGR and SR in the HCF3 group dramatically increased compared to the HC group. With the increase of MLF in the HC diet, the activities of glycolysis and antioxidant enzymes in the liver tended to increase, while the changes of gluconeogenesis-related enzyme activities showed the opposite trend and significantly changed in the HCF3 group. Additionally, MLF supplementation dramatically increased the mRNA expression involved in glycolysis, antioxidative enzymes and anti-inflammatory cytokines in comparison with the HC group. Furthermore, gluconeogenesis and pro-inflammatory cytokine genes' expression dramatically decreased. Furthermore, the proportion of Clostridium and Rhodobacter in the HC group dramatically declined, and the proportion of Lactococcus dramatically increased, compared to the HC group. In addition, 300 mg/kg MLF supplementation significantly improved the species composition and homeostasis of intestinal microbiota. These results indicate that MLF can alleviate the negative effects of low growth performance, glucose metabolism disorder, liver oxidative damage and intestinal microbiota disturbance caused by HC diets, and the relief of MLF is dose-related.